Review of Trichomonas vaginalis in Iran, Based on Epidemiological Situation - M Arbabi; M Delavari; Z Fakhrieh-Kashan; H Hooshyar (JRI, 2018)
Trichomoniasis, which is caused by Trichomonas vaginalis, is the most common non-viral sexually transmitted infection (STI) in the world including Iran. There were roughly 250 million new cases all over the world in a year. T. vaginalis as an important disease has been associated with HIV (in terms of exposure to sexually transmitted infection, STI) which increases the number of high-risk members, and thus it is an important public health problem. Additionally, this pathogen has been associated with serious health consequences. For instance, it may cause a woman to deliver a low-birth-weight or premature infant, and increase chances of cervical cancer. Because little information is available about the prevalence of T. vaginalis infection in Iranian population, this review was carried out to determine the prevalence of T. vaginalis among Iranian population. For this systematic review, data about epidemiology of T. vaginalis in different parts of Iran with different populations were systematically collected from 1992 to 2017 through the international databases such as PubMed, Scirus, ISI Web of Science, Scopus, EMBASE, Science Direct and Google Scholar and Islamic World Science Citation Center (ISC). National database searching included Iran Medex, Iran Doc, Magiran and Scientific Information Database (SID). A total of 39 clinical and laboratory investigations about the prevalence of Trichomoniasis from different regions of Iran were analyzed. The overall prevalence rate of T. vaginalis infection in Iranian population was estimated to be minimally 0.4% and maximally 42%. The present review showed that T. vaginalis infection rate is relatively high among the Iranian population. The control strategies, including personal hygienic education, simultaneous couple treatment, the sensitivity of diagnostic methods, appropriate preventive tool (condom) in sexual contacts could lead to the disruption of transmission.